The Financial Results of Energy Sector Companies in Europe and Their Involvement in Hydrogen Production - Andrzej Chmiela; Adrian Gawęda; Beata Barszczowska; Natalia Howaniec; Adrian Pysz; Adam Smoliński (Energies)
In response to growing environmental concerns, hydrogen production has emerged as a critical element in the transition to a sustainable global economy. We evaluate the impact of hydrogen production on both the financial performance and market value of energy sector companies, using balanced panel data from 288 European-listed firms over the period of 2018 to 2022. The findings reveal a paradox. While hydrogen production imposes significant financial constraints, it is positively recognized by market participants. Despite short-term financial challenges, companies engaged in hydrogen production experience higher market value, as investors view these activities as a long-term growth opportunity aligned with global sustainability goals. We contribute to the literature by offering empirical evidence on the financial outcomes and market valuation of hydrogen engagement, distinguishing between production and storage activities, and further categorizing production into green, blue, and gray hydrogen. By examining these nuances, we highlight the complex relationship between financial market results. While hydrogen production may negatively impact short-term financial performance, its potential for long-term value creation, driven by decarbonization efforts and sustainability targets, makes it attractive to investors. Ultimately, this study provides valuable insights into how hydrogen engagement shapes corporate strategies within the evolving European energy landscape.